A longitudinal study of green industrial performance for the period 2000-2015. (17th March 2020) - Alba, Jaime Moll De; Todorov, Valentin
This article undertakes a longitudinal study of the green industrial performance of a set of 104 economies for 2000 to 2015. Our analysis concludes that industrialised countries continue to lead green industrial performance in 2015, with Denmark, Singapore, the Republic of Korea, Germany and the Czech Republic being the top performers. Selected emerging industrial economies display significant progress. Leading performers have equipped themselves with comprehensive green strategies and policies. Green industrial development seems to offer an untapped potential for developing countries. In this article, we refine an earlier version of our green industrial performance (GIP) index by using a revised definition of green products. We also use new imputation methods of missing values. Finally, our study puts forward a set of recommendations for future research.